(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the pedagogical and psychological problems of the formation of socio-cultural competence, as well as the formation of the sides of the culture of treatment in the formation of socio-cultural competence in the students of a higher educational institution.